1801-PUB: Efficacy and Safety of Once-Weekly Semaglutide in People with Type 1 Diabetes in Real-World Practice - BELLIDO, VIRGINIA; GROS HERGUIDO, NOELIA; AMUEDO, SANDRA; BAENA ARIZA, LUIS; ALFONSO, SOTO M. (Diabetes (New York, N.Y.), 2023)
Introduction: Semaglutide has shown significant improvements in weight and HbA1c in T2D, but the data about the efficacy and safety in people with T1D (PWT1D) are scarce. Aims & Methods: We conducted a retrospective study including adults with T1D and obesity who had initiated once weekly (OW) semaglutide adjunct to insulin, to evaluate its efficacy and safety. Results: Twenty-one subjects were included (52.4% female, mean age 44.2 ± 12.9 years, diabetes duration 19.1 ± 10.8 years, HbA1c 7.7 ± 0.8%, BMI 38.3 ± 5.9 kg/m2). Of them, 47.6% had hypertension, 52.4% dyslipidaemia, 23.8% cardiovascular disease, and 19% renal disease. Mean treatment duration was 30.4 weeks. Mean OW semaglutide dose was 0.8 ± 0.2 mg. Significant reductions in HbA1c (-0,6 ± 0.7%), weight (-8.1 ± 6.1 kg; -7.5 ± 5.8%) and daily insulin dose (-20.7 ± 18.9 U/day) were achieved. An HbA1c reduction of ≥ 0.4% was seen in 61.9% of subjects. Weight loss ≥ 5% and ≥ 10% were achieved in 57.1% and 33.3% of cases, respectively. Significant improvements in time in range (+8.8 ± 13.4%) and time in hyperglycemia >250 mg/dL (-5.3 ± 5.1%) were attained. Four subjects experienced gastrointestinal adverse events, and two of them discontinued treatment. Conclusions: Adjunct treatment with OW semaglutide in PWT1D in a real-life setting resulted in promising results in glycemic control, weight, and insulin requirements, in a safe and well-tolerated manner.